Analysis of miRNA Profiles and the Regulatory Network in Congenital Pulmonary Airway Malformations - Zeng, Jiahang; Liu, Wei; Liang, Jianhua; Peng, Junzheng; Wang, Fenghua; Tang, Jue; Yang, Qinglin; Zhuang, Linwei; Huang, Dongmei; Li, Le (Frontiers in Pediatrics, 2021)
Background: Specific diagnostic markers for congenital pulmonary airway malformations (CPAMs) have not yet been discovered. This study intends to detect differentially expressed miRNAs in type I and II CPAMs by using a miRNA chip and clarify the feasibility of miRNAs as different CPAM typing markers. Methods: Lung tissues of type I and type II CPAMs were collected and used to assess the differentially expressed miRNAs using a miRNA chip after evaluation using hematoxylin–eosin staining and Masson staining. Quantitative reverse transcription-polymerase chain reaction and fluorescence in situ hybridization were used to verify the quality of the miRNA chip. The function and pathways of related differentially expressed miRNAs were analyzed by Gene Ontology Enrichment (GO) analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis, respectively. Targets of miRNAs were predicted by targetscan7.1 and mirdbV6 and the network between miRNA and mRNA was established using Cystoscope software. Results： In total, 394/34 upregulated and 321/72 downregulated miRNAs were found in type I and II CPAMs, respectively. GO and KEGG analysis showed that different pathways are involved in the regulation of CPAM, including platelet activation, Ras, MAPK, FoxO, and PI3K-Akt signaling pathways. miRNA–mRNA network analysis confirmed four major miRNAs in CPAM, including miR-4731-5p to complexin 2, miR-3150a-3p to vesicle amine transport 1, miR-32-5p to F-box and WD repeat domain containing 7, and miR-454-3p to SLAIN motif family member 1. Conclusion: In summary, we have identified four candidate miRNAs and pathways related to different pattern CPAMs, which provide a new perspective for CPAM research and treatment.